Impact of inflammation and Treg cell regulation on neuropathic pain in spinal cord injury: mechanisms and therapeutic prospects - Zhang, Chunjia; Li, Yan; Yu, Yan; Li, Zehui; Xu, Xin; Talifu, Zuliyaer; Liu, Wubo; Yang, Degang; Gao, Feng; Wei, Song; Zhang, Liang; Gong, Han; et al. (Frontiers in Immunology, 2024)
Spinal cord injury is a severe neurological trauma that can frequently lead to neuropathic pain. During the initial stages following spinal cord injury, inflammation plays a critical role; however, excessive inflammation can exacerbate pain. Regulatory T cells (Treg cells) have a crucial function in regulating inflammation and alleviating neuropathic pain. Treg cells release suppressor cytokines and modulate the function of other immune cells to suppress the inflammatory response. Simultaneously, inflammation impedes Treg cell activity, further intensifying neuropathic pain. Therefore, suppressing the inflammatory response while enhancing Treg cell regulatory function may provide novel therapeutic avenues for treating neuropathic pain resulting from spinal cord injury. This review comprehensively describes the mechanisms underlying the inflammatory response and Treg cell regulation subsequent to spinal cord injury, with a specific focus on exploring the potential mechanisms through which Treg cells regulate neuropathic pain following spinal cord injury. The insights gained from this review aim to provide new concepts and a rationale for the therapeutic prospects and direction of cell therapy in spinal cord injury-related conditions.